Studi Komputasi DFT terhadap Stabilitas dan Energi Ikatan Molekul Hidrokarbon Aromatik Polisiklik - Andra Hendrawan (Pure Chemistry Research, 2025)
Polycyclic aromatic hydrocarbons (PAHs) are a class of organic compounds composed of multiple fused aromatic rings, widely studied due to their environmental persistence, stability, and potential health hazards. Understanding their bonding characteristics and stability is crucial for both theoretical and applied chemistry. This study employs Density Functional Theory (DFT) to investigate the stability and bond energies of selected PAH molecules, including naphthalene, anthracene, and pyrene. Computational simulations were conducted using the B3LYP functional with the 6-311G(d,p) basis set. The results demonstrate that the stability of PAHs increases with the number of fused aromatic rings, while bond dissociation energies (BDEs) reveal subtle variations influenced by molecular topology. Frontier molecular orbital (FMO) analysis further indicates that HOMO–LUMO energy gaps decrease as molecular size increases, suggesting enhanced reactivity in larger PAHs. These findings provide insights into the structure–property relationships of PAHs and contribute to a deeper understanding of their stability in environmental and industrial contexts.